Informal institutional change and the place of traditional justice in Sierra Leone's post-war reconstruction. Issue 470 (10th September 2018) - Sesay, Mohamed
Abstract: Engaging traditional authorities in post-conflict development of the rule of law is expected to preserve progressive elements of traditional dispute resolution while reforming the despotic practices of such authorities. However, beyond this widely-held expectation, the peacebuilding literature has so far failed to specify which traditional functions are susceptible to change and the mechanisms for informal institutional change. Based on qualitative fieldwork on traditional justice in Sierra Leone, this article argues that judicial roles which have emerged in response to weaknesses in the modern state system can be destabilized by post-conflict institutional reforms aimed at (re)building the rule of law. This is because the problem-solving needs which precipitated those informal judicial functions can be altered by an effective state system and the cost most likely to inhibit institutional change in this reconstruction context is particularistic to traditional authorities. However, preference for traditional methods and practices outside this endogenous relationship raises a fundamental question about socially-relevant justice which cannot be addressed by a functional state system and whose disruption incurs widely dispersed sociocultural costs.